AGE AND GROWTH OF THREE SPECIES OF SEERFISHES SCOMBEROMORUS COMMERSOU, S. GUTTATUS AND S. L1NEOLATUS - Devaraj, M (Indian Journal of Fisheries, 2011)
Length-frequency an:(lysis indicates that the king seer (Scomberomorus cotnmerson) attains a size of 402 mim, 726 mm, 995 mm and 1186 mm total length at 1, 2, 3, and 4 years of age, respectively, the streaked seer (S. Uneolatus) reaches a size of 350 mm, 713 mm, 835 mm and 965 mm total length et 1, 2, 3 and 4 years, respectively, and the spotted seer (S. guttatus a size of 369 mm, 532 mm: and 640 mm at 1, 2, and 3 years, respectively. Back-calculated lengths of fish at the time of ring formation on otoliths figree closely with the results of lengthfrequency analysis. The maximum lengths of king seer, streaked seer and spotted seer met with in the catches are 1936 mm (33 kg), 980’ mm (4.6 kg) and 705 mm (2.1 kg), respectively. The theoretical maximum lengths (Lac) computed by Bagenal or Rafail method for the von Bertsfeaffy growth equation are found to be 2081 mm (46.7 kg) for the king seer, 1683 mm (15.7 kg) for the male streaked seer, 1447 ram (24.3 kg) for the female streaked seer and 1278 mm (9.6 kg) for the spotted seer. All the three species develop two rings a year in their otoliths at a regular interval of six months. For all the three species, the exponent in the length-weight relationship is found to be close to 3.